2013
DOI: 10.1063/1.4812981
|View full text |Cite
|
Sign up to set email alerts
|

Toward high efficiency of inverted organic solar cells: Concurrent improvement in optical and electrical properties of electron transport layers

Abstract: The conversion efficiency (η) of organic solar cells (OSCs) constructed with ITO/ZnO/P3HT:PCBM/PEDOT:PSS/Ag is improved by incorporating Al into ZnO films (AZO) as electron transport layers (ETLs). Compared with ZnO films, AZO-based OSCs enhance η by ∼13.9% via improving short-circuit photocurrent density from 10.73 to 11.12 mA cm−2 and fill factor from 53.7% to 60.8%. Doping Al into ZnO ETLs not only optimizes band alignment between organic active layers and ETLs and increases carrier concentration, conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…163,193 47,163,193 For the inverted PSCs with AZO CBLs, it is worth noting that the device performances are strongly affected by the crystallinity and stoichiometry of AZO. 193,204 This is because the electronic properties of AZO CBLs, such as work function, conductivity, mobility as well as surface states, are massively Please do not adjust margins Please do not adjust margins determined by the stoichiometry of AZO. 154,164 Tsai and coworkers have investigated the effects of Al content (from 0 to 12 mol.…”
Section: Doping Of Zno Cbls In Inverted Polymer Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…163,193 47,163,193 For the inverted PSCs with AZO CBLs, it is worth noting that the device performances are strongly affected by the crystallinity and stoichiometry of AZO. 193,204 This is because the electronic properties of AZO CBLs, such as work function, conductivity, mobility as well as surface states, are massively Please do not adjust margins Please do not adjust margins determined by the stoichiometry of AZO. 154,164 Tsai and coworkers have investigated the effects of Al content (from 0 to 12 mol.…”
Section: Doping Of Zno Cbls In Inverted Polymer Solar Cellsmentioning
confidence: 99%
“…It is believed that the tunable band-gap combine with the increased carrier concentration and conductivity of AZO films via Al doping, and enhanced optical absorption of P3HT are the reasons of enhanced device performance. 204 Doping ZnO with the group-III elements such as boron (B), gallium (Ga), or indium (In) for doping ZnO CBLs, is another effective way to improve the performance of inverted PSCs. 155,194,195,201 Kyaw et al investigated the correlation between the device performance and the indium contents of the sol-gel derived indium-doped ZnO (IZO) CBL in inverted PSCs.…”
Section: Doping Of Zno Cbls In Inverted Polymer Solar Cellsmentioning
confidence: 99%
“…[32][33][34][35] In parallel, Stubhan et al have demonstrated solution-processed AZO thin fi lms achieved via sol-gel techniques as ETL in P3HT:PC 60 BMbased solar cells, overcoming the inherent thickness-and interface-related issues of intrinsic ZnO. By systematically varying the Al content from 2%-12%, Tsai et al [ 41 ] have shown peak effi ciencies of 3.78% in P3HT:PC 60 BM devices (optimum Al content: 9 mol%) with Al-doped ZnO ETLs processed at 150 °C. AZO thin fi lms functioning as ETL in OPV fl exible modules (P3HT:PC 60 BM; PCE ≈3.1%), [ 38 ] in OPV tandems (PCE ≈4.5%) [ 39 ] and in terms of life time/degradation [ 40 ] has been reported before.…”
mentioning
confidence: 99%
“…By changing the doping concentration of Al, the energy levels in the conduction band of ZnO NPs can be tuned to better match the LUMO levels of different electron acceptor materials. Therefore, the energy level alignment between ETL and electron accepting fullerenes, as well as the built-in potential of the heterojunction, can be further improved 11 13 , 33 , 34 . However, high transparency in the long wavelength is depressed due to metal doped in ZnO.…”
Section: Introductionmentioning
confidence: 99%